LENT Score as a Prognosis Factor for Overall Survival and Progression-Free Survival in Malignant Pleural Effusion Patients at Tertiary Hospitals in West Sumatera, Indonesia - Laisa Azka; Sabrina Ermayanti; Russilawati; Irvan Medison; Deddy Herman; Fenty Anggraininy (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Malignant pleural effusion (MPE) has a variable survival rate and prognosis. The LENT score is one method for assessing survival rates in patients with MPE. This study aimed to investigate the LENT score as a prognostic factor for overall survival (OS) and progression-free survival (PFS) of patients with MPE at a tertiary hospital in West Sumatera. Methods: This study was an observational analytic study involving several tertiary hospitals in West Sumatera with a minimum observation period of 2 years. Data were collected from medical records. We used Kaplan Meier analysis to assess OS and PFS. Results: A total of 198 subjects met the inclusion criteria. Most MPE patients in this study were aged ≥60 years, male, smokers, pleural fluid lactate dehydrogenase value <1500, ECOG 1, serum NLR value <9, and high-risk cancer, namely lung cancer. The distribution of LENT scores for MPE patients was evenly distributed among the low, medium, and high-risk groups. Kaplan Meier analysis showed that the median OS based on LENT scores were 804 days, 275 days, and 161 days, respectively (log-rank test p = 0.000). The median PFS based on LENT scores were 715 days, 202 days, and 106 days, respectively (log-rank test p=0.000). The OS and PFS findings are longer than previous studies. Conclusion: Based on LENT scores, overall survival and progression-free survival MPE patients at tertiary hospitals in West Sumatera have a better prognosis compared to previous studies.